Satellite Navigation in Hydrography - Eaton, R. M.; Wells, D. E.; Stuifbergen, N. (The International Hydrographic Review, 2015)
Satellite Navigation ("Navsat") is a remarkable development in positioning that gives a dozen or more good fixes per day, anywhere in the world. The accuracy of the ship’s position from a good pass is from 60-600 m, depending on how well the ship’s course and speed is measured. For stationary receivers, this positioning accuracy improves to about 20 m. Navsat’s great value to hydrography is that the fix is virtually free of systematic position errors. Navsat is extremely useful in offshore surveys as a complementary partner to a high resolution, continuous system which has systematic biasses or which accumulates error with time; we describe integration with rho-rho (range measuring) Loran-C, and Doppler Sonar. The continuous system feeds accurate course and speed to Navsat, which in turn provides a control network of intermittent, bias-free fixes. By bridging a number of satellite fixes the combined system means out random errors and improves on the single-pass accuracy of Navsat. Navsat has many auxiliary applications. It is used to resolve the cycle ambiguity in low frequency radio aids; to calibrate both marine survey positioning systems and radio aids to navigation; to position the transmitters for the radio aids; to position offshore drilling rigs; and as a geodetic instrument capable of establishing shore control to 1 m accuracy. The “Datum Shift” between a Navsat position and a position from the local geodetic control often causes confusion. We outline the reason for the difference, and give algorithms for computing it.